2009
DOI: 10.4028/www.scientific.net/kem.417-418.873
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Characteristics of Fatigue Crack Propagation for TA15 Titanium Alloy

Abstract: Crack propagation tests are conducted on TA15 titanium alloy in three stress levels to investigate the stochastic characteristics of FCG. A random variable probability FCG model, base on the Paris’ law, is used to characterize the stochastic performance. Distribution significance test has been done, which shows that the random variable X can be considered reasonably to follow log-normal distribution in all the three stress levels. The probability distribution of crack size at any specified loading cycle and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The flowchart of fatigue crack growth probabilistic analysis on the turbine disk at high temperature is shown in Figure 4. The time‐dependent uncertainty in crack growth is modeled by a non‐negative stationary random process, reflecting the uncertainty of material at high temperature referred to Yang's model (Salivar, 1988; Yang, 1982, 2009; Bao, 2010). To justify the applicability of the probabilistic model, fatigue crack growth data at high temperature obtained from the experiments are needed.…”
Section: Probabilistic Design Process For Turbine Disk At High Temperaturementioning
confidence: 99%
“…The flowchart of fatigue crack growth probabilistic analysis on the turbine disk at high temperature is shown in Figure 4. The time‐dependent uncertainty in crack growth is modeled by a non‐negative stationary random process, reflecting the uncertainty of material at high temperature referred to Yang's model (Salivar, 1988; Yang, 1982, 2009; Bao, 2010). To justify the applicability of the probabilistic model, fatigue crack growth data at high temperature obtained from the experiments are needed.…”
Section: Probabilistic Design Process For Turbine Disk At High Temperaturementioning
confidence: 99%
“…Previously, KolmogorovSmirnov's goodness of fit test was used to select the best distribution among five distributions (Normal, 2-parameter lognormal, 3-parameter lognormal, 2-parameter Weibull and 3-parameter Weibull distributions) and based on the test, only the classical lognormal was seen to be suitable for the best fitting distribution for the HDPE structures (Khelif et al, 2008). Another study by Bao et al (2009) found that the crack growth rate could be considered reasonably to follow the log-normal distribution in all the three stress levels (260MPa, 280MPa and 320MPa) and verified by the value from the Chi-Square goodness of fit test. The purpose of this study is to determine the statistical distribution of the two variables: initial crack length and a random number of loading.…”
Section: Related Workmentioning
confidence: 99%